2004
DOI: 10.4049/jimmunol.172.10.6313
|View full text |Cite
|
Sign up to set email alerts
|

Viral FLIP Impairs Survival of Activated T Cells and Generation of CD8+ T Cell Memory

Abstract: Viral FLIPs (vFLIPs) interfere with apoptosis signaling by death-domain-containing receptors in the TNFR superfamily (death receptors). In this study, we show that T cell-specific transgenic expression of MC159-vFLIP from the human Molluscum contagiosum virus blocks CD95-induced apoptosis in thymocytes and peripheral T cells, but also impairs postactivation survival of in vitro activated primary T cells despite normal early activation parameters. MC159 vFLIP impairs T cell development to a lesser extent than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 58 publications
4
48
1
Order By: Relevance
“…Interestingly, two recent reports using transgenic mouse lines with T cell-specific overexpression of cellular c-FLIP L and viral MC159-vFLIP describe suppressed in vitro AICD (although in the case of c-FLIP L AICD in vivo was unaffected [30,42]). T cell death upon TCR restimulation in vitro is driven mostly by CD95 [39], and it is presently unclear why neither FLIP S in our transgenic T cell model nor FLIP L in another transgenic study [23] protect against in vitro AICD, despite the observed resistance against cell death induced by recombinant CD95L.…”
Section: Overexpression Of Flip S Inhibits Cd95l-induced Apoptosis Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, two recent reports using transgenic mouse lines with T cell-specific overexpression of cellular c-FLIP L and viral MC159-vFLIP describe suppressed in vitro AICD (although in the case of c-FLIP L AICD in vivo was unaffected [30,42]). T cell death upon TCR restimulation in vitro is driven mostly by CD95 [39], and it is presently unclear why neither FLIP S in our transgenic T cell model nor FLIP L in another transgenic study [23] protect against in vitro AICD, despite the observed resistance against cell death induced by recombinant CD95L.…”
Section: Overexpression Of Flip S Inhibits Cd95l-induced Apoptosis Inmentioning
confidence: 99%
“…Obviously, the absence of CD95 receptor signaling and blockage of caspase-mediated apoptosis induced by CD95 activation are not functionally equivalent. The difference may be explained by a recently discovered caspase-independent cell death pathway emanating from the CD95 receptor, which involves the death domain-containing kinase RIP [41].Interestingly, two recent reports using transgenic mouse lines with T cell-specific overexpression of cellular c-FLIP L and viral MC159-vFLIP describe suppressed in vitro AICD (although in the case of c-FLIP L AICD in vivo was unaffected [30,42]). T cell death upon TCR restimulation in vitro is driven mostly by CD95 [39], and it is presently unclear why neither FLIP S in our transgenic T cell model nor FLIP L in another transgenic study [23] protect against in vitro AICD, despite the observed resistance against cell death induced by recombinant CD95L.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic mice expressing vFLIP in T cells (CD2-vFLIP) were obtained from the U.S. National Institutes of Health (Bethesda, MD, USA) [31], housed and bred at the Taconic (Germantown, NY, USA) and UFRJ transgenic animal facilities. All animal experiments were approved by the Ethics Committee for Use of Animals of UFRJ, in accordance with national regulations.…”
Section: Animalsmentioning
confidence: 99%
“…It is noteworthy, however, that caspase-8 activity is also required for other aspects of T cell activation and development of immune responses to viral and parasite infections [13, 31, 34 -37]. As we found previously that vFLIP expression negatively affects the production of cytokines by CD8 T cells and CD8 T cell-mediated immunity [31,35], we chose the L. major infection model to explore the effects of caspase-8 inhibition on CD4 T cells. Despite expressing increased Th2 cytokines along with a robust Th1 response, vFLIP mice exerted a better control over L. major infection, with reduced lesions and parasite loads, than WT mice.…”
Section: Introductionmentioning
confidence: 99%